Mineração em unidades de conservação no estado de Minas Gerais - Mendes, Clara Boechat de Lacerda (2017)
Minas Gerais has in its territory three biomes, presenting significant biodiversity, but they are under intense pressure and degradation. To increase protection of the vegetation remaining areas, Conservation Units (UC) were created. Due to physical and geological favorable conditions, this Brazilian state has been standing out among the country's largest mineral producers. As a result, mining threatens and puts pressures on protected areas and their environment. Mineral exploration provides economic growth, thus causing socialenvironmental impacts. Therefore, the objective of this research was to analyze the characteristics of the mining processes overlapping the Conservation Units located in Minas Gerais state and the legislation on the subject, and thus to present the threats and pressures suffered by the UC and its surrounding areas. The Spatial data the Conservation Units and mining processes were obtained from the official sites of the Chico Mendes Institute for Biodiversity Conservation (ICMBio), State Forestry Institute (IEF) and the National Department of Mineral Production (DNPM); to simulate the Damping Zones a radius of 2 km from the boundary of the UC was considered. Using Geographic Information System tools, the layers were analyzed, resulting in the identification of the overlapping mining processes in the UC and their surrounding areas. Of the 41,165 mining processes present in Minas Gerais, 657 are in federal UC and 1,852 in state UC. In the case of simulated Damping Zones, 324 mining processes are affect in the Federal and 1192 in the State UC. The condition of the Minas Gerais Conservation Units and their environment, with respect to the threats and pressures related to mining is alarming. In general, the Sustainable Use Units are more vulnerable in the Atlantic Forest biome. The panorama and the discussions presented in this study show that the mineral policy and legislation do not respect the National Conservation Unit System (SNUC), putting the economic issue against the environmental one more time; compromising not only the conservation objectives associated with the creation of protected areas, but also the products and services essential to life from natural ecosystems.